EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN PERMAINAN TRADISIONAL CONGKLAK TERHADAP MINAT BELAJAR MATEMATIKA (MTK) SISWA SEKOLAH DASAR - Erlin Prasetyo; Nyoto Hardjono (Universitas Borneo Tarakan, 2020)
Abstract: The purpose of this study is to analyze traditional Congklak media in increasing mathematics learning interest (MTK) in elementary school students and to introduce and improve numeracy skills related to the addition and subtraction of elementary school students through Congklak games, and to determine the effect of using Congklak media on interest student learning in mathematics learning. This type of research method used is a meta-analysis of research that has been done before. This study uses a qualitative method. The purpose of this research is to find out the effectiveness of traditional Congklak learning media in improving elementary students' numeracy skills. In collecting this data, research conducted by searching journals through Google Scholar. Keywords used for journal tracing are: Effectiveness, learning media, traditional congklak games, mathematics, elementary school students. The results of the analysis show that the use of traditional learning media in Congklak has increased the interest in learning starting from the lowest at 17.11% to the highest at 135.74% with an average of 44.37%. Keywords: Effectiveness; learning media; traditional congklak games; mathematics; elementary school students.Abstrak: Tujuan penelitian ini adalah untuk menganalisis media permaianan tradisional congklak dalam meningkatkan minat belajar matematika (MTK)pada siswa sekolah dasar danÂ untuk mengenalkan dan meningkatkan kemampuan berhitung terkait operasi penjumlahan dan pengurangan siswa sekolah dasar melalui permainan congklak, serta untuk mengetahui pengaruh penggunaan media congklak terhadap minat belajar siswa dalam pembelajaran matematika . Jenis metode penelitian yang digunakan adalah meta analisis dari penelitian yang telah dilakukan sebelumnya. Penelitian ini menggunakan metode kualitatif. Dari penelitian ini bertujuan untuk mengetahui keefektivitasan media pembelajaran permainan tradisonal congklak dalam meningkatkan kemampuan berhitung siswa sekolah dasar. Dalam pengumpulan data ini, penelitian melakukan dengan mencari jurnal melalui Google Cendekia. Kata kunci yang digunakan untuk penelusuran jurnal adalah:Efektivitas, media pembelajaran, permainan tradisional congklak, matematika,Â siswa sekolah dasar. Hasil analisi menunjukkan bahwa penggunaan media pembelajaran permainan tradisional congklak mengalami peningkatan minat belajar mulai yang paling rendah yaitu 17,11% hingga yang paling tinggi yaitu 135,74% dengan rata-rata sebesar 44,37%.Â